Consider Best Practices to Achieve AMI Installation Success. Issue 10 (8th October 2019) - Butler, Thomas
Abstract : For a water utility of any size to function properly, effective meter reading is a vital aspect of daily operations. Meter reading supports both ends of the transaction, ensuring water is properly delivered and accounted for and customers are billed accordingly each month. Any significant meter innovation or improvement could greatly benefit a water utility.